Characterization of transparent conducting carbon nanotube thin films prepared via different methods - Iskandar Yahya,; Lee, Li Theng; Seri Mastura Mustaza,; Huda Abdullah,; Nowshad Amin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The fabrication and characterization of transparent conductors based on single walled carbon nanotube (SWCNT) thin films were carried out in controlled environment and its performance compared. Here, we demonstrate the fabrication of thin, transparent, optically homogeneous, electrically conducting films of metallic enriched single-walled carbon nanotubes via three different deposition techniques namely dip coating, vacuum filtration and Langmuir Blodgett. Optical characterization showed that the maximum transmittance, TM, in Vis region is ~ 96.3% and minimum surface roughness, Ra ~ 4.87 nm achieved via Langmuir-Blodgett technique. I-V characteristics shows minimum sheet resistance, Rs ~ 3.62 × 103 Ω/sq and maximum conductivity, σ ~ 27.65 Ω-1cm-1 for vacuum filtration technique. It is shown that SWCNT deposition technique significantly affects the optical and electrical characteristics of resulting thin films. Langmuir Blodgett method produced film with the lowest surface roughness of Ra ~ 4.87 nm and uniform conductivity of σ ~ 0.025 Ω-1cm-1, whereas vacuum filtration method produced film with the highest surface roughness of Ra ~ 12.83 nm and non-uniform conductivity, σ, ranging from ~ 0.199 to ~0.017 Ω-1cm-1 depending on the film dimensions.